Crystalline polyaryletherketone-based porous nanoparticle composite membranes, methods of preparation, and uses thereof
Patent Information
- Application Number
- CN202511639635.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-11-11
AI Technical Summary
本发明充分解决了聚芳醚酮类材料难以溶液成膜以及与纳米材料界面缺陷等问题,通过优化实验条件得到了具有优异耐溶剂性能及分离性能的结晶聚芳醚酮基多孔纳米粒子复合膜
1、本发明以聚芳醚酮前驱体为聚合物基质,以多孔纳米材料为填料,制备了复合膜,通过酸热处理实现聚合物基质结晶收缩,分离界面重组,实现聚合物和填料的界面缺陷修复,提升分离膜的分离性能;
Smart Images

Figure CN121082126B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of separation materials technology, specifically relating to a crystalline polyarylether ketone-based porous nanoparticle composite membrane, its preparation method and its application, particularly in the fields of molecular separation such as water treatment, dye separation, molecular sieving or drug purification. Background Technology
[0002] Compared to traditional separation methods, organic solvent nanofiltration membrane separation technology is considered a more energy-efficient and effective separation technology due to its feasible operation, superior efficiency, and low energy consumption. However, traditional polymer membranes exhibit a "trade-off effect" in the presence of organic solvents and suffer from poor stability. Therefore, there is an urgent need to manufacture membranes with excellent solvent resistance, high permeability, and selectivity, which is of great significance to the field of molecular sieving.
[0003] Among numerous methods for preparing separation membranes, blending novel porous materials with polymers can combine the excellent processing properties of polymers with the good permeation and sieving properties of porous materials. This is beneficial for maintaining the application potential of membranes in large-scale preparation while potentially overcoming the limitations of the trade-off effect in the application of traditional polymer membranes in molecular sieving. The core of mixed matrix membrane design lies in the selection of polymer matrix and filler. Semi-crystalline polyaryletherketone (PEEK), as an engineering plastic, has excellent thermal stability, mechanical properties, and solvent resistance, making it one of the ideal choices for polymer matrix in mixed matrix membranes. Porous materials such as covalent organic frameworks (COF), covalent organic polymers (COP), metal-organic frameworks (MOF), and hydrogen-bonded organic frameworks (HOF) have great potential in organic solvent nanofiltration due to their high specific surface area, inherent nanoscale channels, tunable pore structure, and excellent chemical stability. However, interface defects between polymers and fillers are unavoidable in the preparation of mixed matrix membranes, which significantly reduces the molecular sieving performance of the membrane during separation. Summary of the Invention
[0004] The purpose of this invention is to provide a crystalline polyarylether ketone-based porous nanoparticle composite membrane, its preparation method, and its application.
[0005] This invention utilizes a polyaryletherketone (PAK) precursor containing a ketimine structure as the polymer matrix and porous nanomaterials as the filler, employing an acid-heat treatment method to implement a crystallization-induced shrinkage strategy to prepare a crystalline PAK-based porous nanoparticle composite membrane. This invention effectively solves the problems of the difficulty in solution-forming PAK materials and interfacial defects with nanomaterials. By optimizing experimental conditions, a crystalline PAK-based porous nanoparticle composite membrane with excellent solvent resistance and separation performance was obtained. On the one hand, it realizes the transformation of the PAK precursor containing the ketimine structure into a semi-crystalline PAK; on the other hand, through crystallization shrinkage, it achieves interfacial recombination between PAK and blended porous nanomaterials (such as covalent organic frameworks, covalent organic polymers, metal-organic frameworks, hydrogen-bonded organic frameworks, etc.), repairing polymer-filler interfacial defects and improving separation performance. The crystalline polyaryletherketone-based porous nanoparticle composite membrane prepared by this invention achieves uniform dispersion of nanomaterials on a PEEK substrate, possesses excellent thermal stability, solvent stability, and superior separation performance, which is conducive to the large-scale application of nanofiltration membranes based on porous nanomaterial mixed matrix in water treatment, dye separation, and drug purification.
[0006] The preparation method of the crystalline polyarylether ketone-based porous nanoparticle composite membrane according to the present invention comprises the following steps: (1) The polyarylether ketone precursor polyarylether amine (PAEN), the pore-forming agent, and the nanomaterials are added to an organic solvent and stirred at room temperature to dissolve, resulting in a uniformly mixed casting solution. The solution is then left to stand overnight to remove bubbles. The pore-forming agent is one or more of polyvinylpyrrolidone and polyethylene glycol, and the nanomaterials are one or more of covalent organic framework materials, metal-organic framework materials, covalent organic polymers, and hydrogen-bonded organic framework materials. In the casting solution, the mass fraction of polyarylether amine is 10-18%, the mass fraction of the pore-forming agent is 1-10%, and the mass fraction of the nanomaterials is 1-10%. The structural formula of polyarylether ketone precursor polyarylether amine is shown below. ; Where x, y, a, and b are positive integers, b ≥ 1, and n is a positive integer representing the degree of aggregation; (2) Pour the casting solution obtained in step (1) onto a clean glass plate, scrape the film with a glass rod, and place it into a coagulation bath after evaporation for 8-15 seconds. A polyarylene ether amine mixed matrix porous membrane is then prepared on the glass plate. (3) The polyarylether amine mixed matrix porous membrane obtained in step (2) is added to an acid solution and then reacted in a reactor at 110~170℃ for 3~8h; finally, it is washed with water and ethanol 3~6 times respectively to obtain the crystalline polyarylether ketone porous nanoparticle composite membrane. The structural formula of polyaryletherketone is shown below. ; Where x, y, a, and b are positive integers, b≥1, and n is a positive integer representing the degree of aggregation.
[0007] Preferably, the organic solvent in step (1) is one or more of N-methylpyrrolidone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran; Preferably, the solvent for the coagulation bath in step (2) is one or more of ultrapure water, deionized water, ethanol, and hydrochloric acid. Preferably, the acid used in step (3) is one or more of hydrochloric acid, sulfuric acid, phytic acid, sulfosalicylic acid, benzenesulfonic acid, acetic acid, and p-toluenesulfonic acid, with a concentration of 0.1~5M; The crystalline polyaryletherketone-based porous nanoparticle composite membrane of the present invention is prepared by the above method.
[0008] This invention also provides applications of the above-mentioned crystalline polyarylether ketone-based porous nanoparticle composite membrane in molecular separation fields such as water treatment, dye separation, molecular sieving, or drug purification (some applications are as follows). Figure 5 , Figure 7 and Figure 8 (As shown).
[0009] The beneficial effects of this invention are as follows: 1. This invention uses polyaryletherketone precursor as polymer matrix and porous nanomaterials as filler to prepare a composite membrane. By acid heat treatment, the polymer matrix crystallizes and shrinks, and the separation interface is reorganized, thereby repairing the interface defects between the polymer and the filler and improving the separation performance of the membrane. 2. In this invention, both the polymer matrix (semi-crystalline polyaryletherketone) and the filler (covalent organic framework material, metal-organic framework material) have good stability and solvent resistance, which is beneficial for the application of membrane materials under real organic solvent nanofiltration conditions. Attached Figure Description
[0010] Figure 1 It is the chemical reaction formula for the transformation of polyaryletherketone precursor to polyaryletherketone during the acid heat treatment process in this invention; Figure 2 These are the infrared spectra of the PAEN / COF-based hybrid matrix porous membrane prepared in step (1) of Example 1 and the PEEK / COF composite membrane prepared in Example 1; Figure 3 These are X-ray diffraction spectra of the PAEN / COF-based hybrid matrix porous membrane prepared in step (1) of Example 1 and the PEEK / COF composite membrane finally prepared in Example 1; Figure 4The stress-strain curves are those of the PAEN membrane prepared in Example 5, the PAEN / COF-based hybrid matrix porous membrane prepared in Example 1, and the PEEK / COF composite membrane. Figure 5 This is a comparison chart of the Congo red retention capacity and ethanol permeability of PEEK / COF composite membranes obtained at different treatment temperatures in Examples 1-4; Figure 6 These are scanning electron microscope images of the surface and cross-section of the PAEN / COF-based mixed matrix porous membrane prepared in step (1) of Example 1, and the PEEK / COF composite membranes prepared in Examples 1 and 2. Figure 7 This is a comparison chart of the Congo red retention capacity and ethanol permeability of the PEEK / COF composite membranes prepared in Examples 1 and 5-8; Figure 8 This is a comparison of the Congo red retention of the PEEK / COF composite membrane prepared in Example 1 after immersion in different organic solvents and heating at 100°C for 3 days. Detailed Implementation
[0011] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. The described embodiments are only some embodiments of the present invention, and not all embodiments. All embodiments based on the present invention fall within the protection scope of the present invention.
[0012] Example 1: (1) Dissolve 1g PAEN, 0.4167g PVP, and 0.6667g COF powder in 6.25g N-methylpyrrolidone, stir evenly at room temperature, and let stand overnight to remove bubbles to obtain casting solution; in casting solution, the mass fraction of PAEN is 12%, the mass fraction of polyvinylpyrrolidone is 5%, the mass fraction of COF is 8%, and the mass fraction of N-methylpyrrolidone is 75%; (2) Pour the obtained casting solution onto a clean glass plate, scrape the film with a glass rod, evaporate for 10 seconds, and then place it in a deionized water coagulation bath to prepare a PAEN-based mixed matrix porous membrane on the glass plate. (3) Prepare a 2M hydrochloric acid solution, add the PAEN-based mixed matrix porous membrane obtained in step (2) into the hydrochloric acid solution, and then put it into a reaction vessel and react at 150°C for 5 hours; finally wash with water and ethanol 4 times respectively to obtain the crystalline polyaryletherketone-based porous nanoparticle (PEEK / COF) composite membrane. (4) The surface, cross-sectional morphology and separation performance of the synthesized PEEK / COF composite membrane were tested.
[0013] Example 2: The difference between Example 2 and Example 1 is that the reaction temperature in step (3) is 110°C, while the other conditions are exactly the same.
[0014] Example 3: The difference between Example 3 and Example 1 is that the reaction temperature in step (3) is 130°C, while the other conditions are exactly the same.
[0015] Example 4: The difference between Example 4 and Example 1 is that the reaction temperature in step (3) is 170°C, while the other conditions are exactly the same.
[0016] Example 5: The difference between Example 5 and Example 1 is that in step (1), the mass of COF powder is 0g and the mass of N-methylpyrrolidone is 6.92g, while the other conditions are exactly the same.
[0017] Example 6: The difference between Example 6 and Example 1 is that in step (1), the mass of COF powder is 0.0833g and the mass of N-methylpyrrolidone is 6.83g, while the other conditions are exactly the same.
[0018] Example 7: The difference between Example 7 and Example 1 is that in step (1), the mass of COF powder is 0.1667g and the mass of N-methylpyrrolidone is 6.75g, while the other conditions are exactly the same.
[0019] Example 8: The difference between Example 8 and Example 1 is that in step (1), the mass of COF powder is 0.4167g and the mass of N-methylpyrrolidone is 6.50g, while the other conditions are exactly the same.
[0020] Examples 1-4 are similar in that the concentrations of each component in the casting solution are the same, i.e., the mass fraction of PAEN is 12%, the mass fraction of polyvinylpyrrolidone is 5%, the mass fraction of COF is 8%, and the mass fraction of N-methylpyrrolidone is 75%. The difference lies in the processing temperature. Examples 1 and 5-8 are similar in that the processing temperature is 110℃~170℃. The difference lies in the mass of COF powder and the mass of N-methylpyrrolidone.
[0021] like Figure 1 As shown, this indicates that during the acid heat treatment process, the polyaryletherketone precursor is transformed into polyaryletherketone; like Figure 2 As shown, the horizontal axis represents the wavenumber (cm). -1 The vertical axis represents transmittance; it can be seen that the PEEK / COF composite membrane at 1650 cm⁻¹... -1 The presence of a C=O bond vibration peak indicates that the transformation from ketoimine to polyaryletherketone has been successfully achieved. like Figure 3 As shown, the horizontal axis represents the 2θ angle, and the vertical axis represents the diffraction intensity. In the figure, both the PAEN / COF-based mixed matrix porous membrane and the PEEK / COF composite membrane can detect the (100), (200), (110), and (001) crystal planes of COF. Compared with the PAEN / COF-based mixed matrix porous membrane, the PEEK / COF composite membrane shows the semi-crystalline peaks of PEEK, which belong to the (110), (111), (200), and (211) crystal planes, indicating that the transformation from amorphous PAEN to semi-crystalline PEEK has been successfully completed. like Figure 4 As shown, the horizontal axis represents elongation and the vertical axis represents tensile strength; this indicates that the PEEK / COF composite membrane prepared by this invention has high mechanical strength and is suitable for practical membrane separation processes. like Figure 5 As shown, the horizontal axis represents the treatment temperature (°C), where the pristine term on the horizontal axis represents the original PAEN / COF-based hybrid matrix porous membrane without acid heat treatment; the vertical axis (left) represents the ethanol permeability (L m). -2 h -1 bar -1 The vertical axis (right) represents the Congo red rejection rate (%). The ethanol permeability and Congo red rejection rate were tested using a dead-end filtration device (see literature Adv. Sci. 2023, 2302654), indicating that the present invention has prepared a composite membrane with organic solvent nanofiltration performance. like Figure 6 As shown, A and D are scanning electron microscope (SEM) images of the surface and cross-section of the PAEN / COF-based mixed matrix porous membrane prepared in step (1) of Example 1; B and E are SEM images of the surface and cross-section of the PEEK / COF composite membrane prepared in Example 1; and C and F are SEM images of the surface and cross-section of the PEEK / COF composite membrane prepared in Example 2. This indicates that the composite membrane prepared at 150°C in Example 1 has a denser surface and a thicker selective layer compared to the PAEN / COF mixed matrix porous membrane and the PEEK / COF membrane obtained by low-temperature treatment in Example 2. This demonstrates that interfacial recombination of the polymer and filler occurred during the acid heat treatment at 150°C, resulting in a denser surface. like Figure 7 As shown, the horizontal axis represents the mass fraction (wt%) of COF powder relative to the polymer matrix, and the vertical axis (left) represents the ethanol permeability (L m). -2 h -1 bar -1 The vertical axis (right) represents the Congo red rejection rate (%). like Figure 8As shown, the horizontal axis represents the name of the organic solvent, and the vertical axis represents the Congo red rejection rate; this indicates that the composite membrane still maintains a high molecular sieving ability after being treated under harsh conditions, and has excellent solvent resistance.
Claims
1. A method for preparing a crystalline polyarylether ketone-based porous nanoparticle composite membrane, characterized in that: The steps are as follows: (1) The polyaryletherketone precursor polyaryletheramine, the pore-forming agent and the nanomaterials are added to an organic solvent and stirred at room temperature to dissolve, resulting in a uniformly mixed casting solution. The solution is left to stand overnight to remove bubbles. The pore-forming agent is one or more of polyvinylpyrrolidone and polyethylene glycol, and the nanomaterials are one or more of covalent organic framework materials, metal-organic framework materials, covalent organic polymers and hydrogen-bonded organic framework materials. In the casting solution, the mass fraction of the polyaryletherketone precursor polyaryletheramine is 10-18%, the mass fraction of the pore-forming agent is 1-10%, and the mass fraction of the nanomaterials is 1-10%. The organic solvent is one or more of N-methylpyrrolidone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide and tetrahydrofuran. The structural formula of polyarylether ketone precursor polyarylether amine is shown below. ; Where x, y, a, and b are positive integers, b ≥ 1, and n is a positive integer representing the degree of aggregation; (2) Pour the casting solution obtained in step (1) onto a clean glass plate, scrape the film with a glass rod, and place it in a coagulation bath after evaporation for 8-15 seconds. A polyarylene ether amine-based mixed matrix porous membrane is prepared on the glass plate. The solvent of the coagulation bath is one or more of ultrapure water, deionized water, ethanol, and hydrochloric acid. (3) The polyarylether amine mixed matrix porous membrane obtained in step (2) is added to an acid solution and then reacted in a reactor at 110~170 °C for 3~8 h; finally, it is washed with water and ethanol 3~6 times respectively to obtain the crystalline polyarylether ketone porous nanoparticle composite membrane; the acid is one or more of hydrochloric acid, sulfuric acid, phytic acid, sulfosalicylic acid, benzenesulfonic acid, acetic acid, and p-toluenesulfonic acid, with a concentration of 0.1~5 M; The structural formula of polyaryletherketone is shown below. ; Where x, y, a, and b are positive integers, b≥1, and n is a positive integer representing the degree of aggregation.
2. A crystalline polyarylether ketone-based porous nanoparticle composite membrane, characterized in that: It is prepared by the preparation method described in claim 1.
3. The application of the crystalline polyarylether ketone-based porous nanoparticle composite membrane according to claim 2 in the fields of water treatment, dye separation, molecular sieving or drug purification.
Citation Information
Patent Citations
Continuous fiber-reinforced polyaryletherketone composite material and preparation method thereof
CN110387119A
Polyaryletherketone separation membrane or sulfonated polyaryletherketone separation membrane with adjustable pore diameter and preparation method thereof
CN110841493A
Polyaniline / polyaryletherketone composite membrane with electrochemical response as well as preparation method and application of polyaniline / polyaryletherketone composite membrane
CN114870638A
